PERAN ORANG TUA DALAM MEMBENTUK KARAKTER SYUKUR PADA ANAK DI MASA KBM DARING PANDEMI COVID-19 - Rizka Dwi Fajriyah Darmayanti; Adhika Putri Syafrina Bukka; Imamul Arifin (Atta'dib Jurnal Pendidikan Agama Islam, 2022)
The Covid-19 pandemic that has spread in the country since early March 2020 has changed almost all activities, including educational activities. The teaching and learning process, which is usually carried out in schools, must move from the homes of each student with the help of information technology. Learning from home activities require more roles from parents in accompanying their children. This article aims to identify the various roles of parents in forming the character of gratitude in children during the Covid-19 pandemic in terms of the `aspect of Islamic education. The sources of information in this research are observation, library research and confirming the statements of several parents interviewed. The author raised this theme because he wanted to contribute knowledge that was beneficial to society.